Ficus carica L - Mohammad Rahimi, Muhammad Aiman; Sakimin, Siti Zaharah; Ramlan, Mohd Fauzi (Universiti Putra Malaysia Press, 2019)
Ficus carica L. or fig is the oldest fruit tree that being cultivated by man. Grouped under genus Ficus, this species is grown widely in Mediterranean region and now being cultivated in an area with temperate or sub-temperate climate. Fig planting in Malaysia is still new, which was brought by a man as a hobby at first. Fig is a unique fruit tree as some variety can produce fruits without pollination. Contain lots of carbohydrates, essential amino acids, vitamins and minerals such potassium, fibre, calcium, iron compared to other fruits, fig have become an important source of diet to people especially in Mediterranean region since ancient time.